Trends of genetic screening in patients with pheochromocytoma and paraganglioma: 15‐year experience in a high‐volume tertiary referral center. Issue 6 (8th January 2018) - Asban, Ammar; Kluijfhout, Wouter P.; Drake, Frederick T.; Beninato, Toni; Wang, Elizabeth; Chomsky‐Higgins, Kate; Shen, Wen T.; Gosnell, Jessica E.; Suh, Insoo; Duh, Quan‐Yang
Abstract : Background and Objectives: Genetic testing for pheochromocytoma and paraganglioma allows for early detection of hereditary syndromes and enables close follow‐up of high‐risk patient. We investigated the trends in genetic testing among patients at a high‐volume referral center and evaluated the prevalence of pheochromocytomas and paragangliomas. Methods: We reviewed the charts of 129 patients who underwent adrenalectomy for pheochromocytoma and paraganglioma between January 2000 and July 2015. To evaluate for trends in genetic testing, patients were divided by year of diagnosis: 2000‐2005 (group 1, n = 35), 2006‐2010 (group 2, n = 44), and 2011‐2015 (group 3, n = 50). Results: Among 129 patients the mean age was 47 years and 56% were women. Groups 2 and 3 were more frequently referred for genetic consultation than group 1, 73%, and 94% versus 26% ( P < 0.001). A total of 67% followed up on the referral. The prevalence of genetic mutation was 50% (21/42 tested). The percentage with a genetic syndrome was 23%, 28%, and 22% respectively for groups 1, 2, and 3. Conclusions: Referral for genetic counseling significantly increased in the past 15 years. However, only two‐thirds of patients followed up with genetic counselors and, therefore, clinicians can do more to improve the adherence rate for genetic counseling.